Emotional intelligence and psychological well-being in nursing professionals from southern Chile - Alex Leandro Veliz Burgos; Anita Patricia Dörner Paris; Alexis Soto Salcedo; Jose Luis Reyes Lobos; Francisco Ganga Contreras (Medisur)
Foundation: Health professionals and specialy those related to caring, are under certain situations which produce professional stress that affect their psychological state. Objective: to identify the levels of emotional intelligence and psychological wellbeing, respectively, in nursing professionals of the Los Lagos Region, Chile. Methods: Descriptive study with non-experimental design. A number of 97 nurses from the Los Lagos region were included. A Trait Meta-Mood Scale and the Ryff scale of psychological wellbeing were applied to evaluate the emotional intelligence and psychological wellbeing respectively, both with good levels of reliability and composed by a series of sub-scales or dimensions. Results: regarding emotional intelligence, high levels of of emotional perception were observed (35 %), emotional comprehension (36,1 %) and emotional regulation (42,7 %). A 57,5 % of the professionals had a high level of psychological wellbeing, although 33,7 % showed  low level of positive relations. Conclusion: there is a direct and significant relation between the scales of emotional intelligence and psychological wellbeing.